2009
DOI: 10.1603/022.038.0319
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal ofTrichogramma ostriniae(Hymenoptera: Trichogrammatidae) in Potato Fields

Abstract: The dispersal ability of Trichogramma ostriniae Pang and Chen, a biological control agent of Ostrinia nubilalis Hübner, was studied in commercial potato fields on the Eastern Shore of Virginia. The purpose was to quantify dispersal of T. ostriniae after an inundative release to aid in determining the number of release points needed per unit area for effective biological control of O. nubilalis in solanaceous crops. A single release of approximately 0.5 million wasps was made in two spatially separate potato fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
1
17
1
4
Order By: Relevance
“…Different from the dispersion capacity observed for T. pretiosum in soybean fields in our results, Chapman et al (2009), studying the dispersal capacity of T. ostriniae in potato fields, observed that this species dispersed rapidly over large distances, successfully moving throughout a 0.4-ha area of potatoes and reproducing at 45 m from the releasing point four days after the release. Chapman et al (2009) results are similar to what was reported for the same parasitoid species in sweet corn by Wright et al (2001). The differences from our results to the literature might be due to both the different studied species, but more probably are due to the differences in crop architecture and plant density in the field.…”
Section: Discussioncontrasting
confidence: 99%
“…Different from the dispersion capacity observed for T. pretiosum in soybean fields in our results, Chapman et al (2009), studying the dispersal capacity of T. ostriniae in potato fields, observed that this species dispersed rapidly over large distances, successfully moving throughout a 0.4-ha area of potatoes and reproducing at 45 m from the releasing point four days after the release. Chapman et al (2009) results are similar to what was reported for the same parasitoid species in sweet corn by Wright et al (2001). The differences from our results to the literature might be due to both the different studied species, but more probably are due to the differences in crop architecture and plant density in the field.…”
Section: Discussioncontrasting
confidence: 99%
“…oculator (0.009-0.341). In this sense, it must be pointed out that Trichogramma species present proper and quick -and even higher -direct dispersion (Chapman et al 2009) particularly if performed through phoresy (Fatouros et al 2005). Nevertheless, it must be pointed out that there may be differences between the amounts of devoted time among the patches (data not available for these species).…”
Section: Discussionmentioning
confidence: 99%
“…For pest control, measurements of pest insect dispersal are essential for establishing the scale over which management should operate, identifying suitable habitat and assessing connectivity between populations (Mahroof et al , 2010), whereas quantifying population densities and survivorship allows the effective monitoring of management outcomes. Data on the movement of introduced control agents for biological control of pests or weeds is also crucial for predicting their spread from release points (Corbett & Rosenheim, 1996; Bianchi et al , 2009; Moerkens et al , 2010), monitoring their populations and predicting impacts on nontarget species (Rudd & McEvoy, 1996; Chapman et al , 2009). Conservation of beneficial insects requires dispersal data to delimit management units and the movement of pollinator species is also becoming increasingly important for restoration of pollinator services in degraded ecosystems (Menz et al , 2010), as well as assessing the risks of engineered genes escaping from genetically‐modified crops (Ellstrand, 2003).…”
Section: Introductionmentioning
confidence: 99%